Mis‐annotations of a promising antibiotic target in high‐priority gram‐negative pathogens. Issue 9 (24th January 2020) - Impey, Rachael E.; Lee, Mihwa; Hawkins, Daniel A.; Sutton, J. Mark; Panjikar, Santosh; Perugini, Matthew A.; Soares da Costa, Tatiana P.
Abstract : The rise of antibiotic resistance combined with the lack of new products entering the market has led to bacterial infections becoming one of the biggest threats to global health. Therefore, there is an urgent need to identify novel antibiotic targets, such as dihydrodipicolinate synthase (DHDPS), an enzyme involved in the production of essential metabolites in cell wall and protein synthesis. Here, we utilised a 7‐residue sequence motif to identify mis‐annotation of multiple DHDPS genes in the high‐priority Gram‐negative bacteria Acinetobacter baumannii and Klebsiella pneumoniae . We subsequently confirmed these mis‐annotations using a combination of enzyme kinetics and X‐ray crystallography. Thus, this study highlights the need to ensure genes encoding promising drug targets, like DHDPS, are annotated correctly, especially for clinically important pathogens. PDB ID: 6UE0 . Abstract :